Períodos de interferência de plantas daninhas na fase inicial de crescimento do eucalipto - Tarouco, Camila Peligrinotti; Agostinetto, Dirceu; Panozzo, Luís Eduardo; Santos, Leo Silva dos; Vignolo, Gerson Kleinick; Ramos, Luiz Otavio de Oliveira (Pesquisa Agropecuária Brasileira, 2010)
The objective of this work was to determine the interference periods of weeds on the growth and development of eucalyptus. The experiment was done in the field from August 2006 to April 2008, with a hybrid of Eucalyptus grandis x Eucalyptus urophylla planted in a randomized block design, with three replicates. Treatments consisted of coexistence and control periods of weeds with eucalyptus culture. During the coexistence treatment, the culture was maintained in the presence of weeds by increasing initial periods of 0, 30, 60, 90, 120, 150, 180, 210, 240, 270, 300, 330 and 360 days after culture transplant (DAT). During the control treatment, the culture was maintained free from weeds for the same periods above described; weeds emerged after those intervals were no longer controlled. Evaluations were made at 360 and at 630 DAT. The competition with weeds caused reduction of the stem diameter and of the dry matter of stems and shoots. Weed control, in the first year of the eucalyptus culture, must be adopted at the end of the period before interference, which happens 107 days after the culture transplant.